Islands of the Ottoman Empire (Princeton)
xix, 148 sayfa
Keywords: “The Ottoman Empire stretched from the Black Sea to the Indian Ocean and the Atlantic. It included islands such as Cyprus, Crete, Rhodes, and many smaller ones in the Aegean, Adriatic, and Black Seas. These islands were its frontiers, and many of the battles against Christian enemies were fought here; they were also bridges to the outside world beyond the empire. They were often fortified by magnificent castles, and sometimes served as bases for corsairs. The chapters deal with significant events in naval history, collective punishments by invaders, and many aspects of economic and cultural life on the islands“ --